TMOD-06. MALIGNANT TRANSFORMATION OF PLEXIFORM NEUROFIBROMAS IN AN NF1 MUTANT MOUSE MODEL OF SPINAL IRRADIATION. (9th November 2020) - Nakamura, Jean; Laurent, Danny; Smith, Abbi; Bessler, Waylan; Clapp, Wade; Horvai, Andrew
Abstract: PURPOSE: Understanding the relationships between ionizing radiation (IR) and carcinogenesis, as well as other variables, including genetic background and sex, may minimize risks of transformation from benign to aggressive cancers while maintaining treatment efficacy. We aim to understand the relationship between IR, tumor microenvironments, and effect of sex on malignant transformation using a conditional knockout mouse model of Neurofibromatosis type 1 (NF1). METHODS: Conditional knockout mouse models of plexiform neurofibromas ( PeriCre + ; Nf1 fl/fl and PeriCre + ; Nf1 fl/ -, n = 172) were treated with 0 Gy; 3 Gy x 5; 3 Gy x 10 of focal, fractionated spinal irradiation (SI) and aged until signs of illness. Histopathological analysis was performed on images from H&E-stained FFPE peripheral nerve tissues. RESULTS: SI affected the survival of mice in a dose-dependent manner, with a significant decrease at 30Gy (median survival 254 and 218 days for 0 Gy and 30 Gy, p < 0.01, Log-rank test). Male mice had reduced overall survival at 15 and 30 Gy (median survival 368, 278 and 245 days for 0, 15 and 30Gy, p < 0.01, Log-rank test), but not in female mice, indicating sex-specific radiosensitivity. Differences in tumour microenvironments did not affect mouse survival after SI. Histopathological analysis is ongoing (43 out of 76 FFPE samples analyzed). Preliminary findings showed a total of 43 malignancies ranging from plexiform neurofibromas (PNs) to high-grade malignant peripheral nerve sheath tumours (MPNSTs). Increasing histologic aggressiveness was observed in higher SI doses, with high-grade MPNST (2.3%) exclusively found in mice irradiated at 30 Gy. CONCLUSION: We present a novel mouse model to study malignant transformation in the context of NF1. Preliminary findings suggest increased malignant transformation at high doses of SI.